1998
DOI: 10.1007/bf03012018
|View full text |Cite
|
Sign up to set email alerts
|

Densities of cerebrospinal fluid and spinal anaesthetic solutions in surgical patients at body temperature

Abstract: Densities of cerebrospinal fluid and spinal anaesthetic solutions in surgical patients at body temperaturePurpose: To determine the densities of cerebrospinal fluid (CSF) in patients for surgery under spinal anaesthesia. The densities of the CSF were compared with the densities of local anaesthestic solutions and their mixtures with commonly used spinal opioids. Method: One ml of CSF was collected from 131 consecutive patients that consented to the study at the time of spinal anaesthesia. Densities were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0
7

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 15 publications
4
89
0
7
Order By: Relevance
“…11 Dextrose-free (plain) solutions of bupivacaine and opioids, usually referred to as being isobaric, are actually hypobaric at body temperature, with a density less than 1.00000 g·mL -1 . 3,[12][13][14] The slight hypobaricity of plain solutions relative to CSF (0.00060 g·mL -1 of difference), could explain the rapid, high sensory block observed after administration of plain local anesthetics and lipid-soluble opioids. 10,11,[15][16][17] Moreover, this pattern of cephalad spread might facilitate the antinociceptive effects of intrathecal opioids through dual activation of spinal as well as supraspinal receptor sites of action, 18 which in turn, might augment the quality of analgesia of plain local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…11 Dextrose-free (plain) solutions of bupivacaine and opioids, usually referred to as being isobaric, are actually hypobaric at body temperature, with a density less than 1.00000 g·mL -1 . 3,[12][13][14] The slight hypobaricity of plain solutions relative to CSF (0.00060 g·mL -1 of difference), could explain the rapid, high sensory block observed after administration of plain local anesthetics and lipid-soluble opioids. 10,11,[15][16][17] Moreover, this pattern of cephalad spread might facilitate the antinociceptive effects of intrathecal opioids through dual activation of spinal as well as supraspinal receptor sites of action, 18 which in turn, might augment the quality of analgesia of plain local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal morphine provides prolonged, good quality postoperative analgesia, while fentanyl has the advantage of decreasing visceral sensation and may prolong the duration of anesthesia. 3,4 In vitro studies examining the effect of adding opioids to local anesthetics have shown morphine to cause minimal change in baricity of the final solution, whereas fentanyl decreases the density of 0.5% bupivacaine by up to 0.0011 g·mL -1 , 5,6 where a difference of as little as 0.0006 g·mL -1 in density alters the movement of local anesthetics in a spinal model. 2 In a more recent study, our group found that the addition of fentanyl to 0.5% bupivacaine made the resultant solution hypobaric within simulated CSF in a spinal model, leading to increased upward spread.…”
Section: Discussionmentioning
confidence: 99%
“…Nilai densitas cairan serebrospinal akan lebih rendah pada wanita dibandingkan dengan laki-laki, 7 wanita hamil dibandingkan dengan yang tidak hamil, 8 dan wanita premenoupause dibandingkan dengan wanita yang sudah menopause. 9 Menurut teori, perbedaan ini akan menyebabkan perubahan barisitas obat anestesi lokal pada kelompok pasien yang berbeda, tetapi perbedaan itu kecil dan mungkin tidak penting secara klinis. 6 Bupivakain 0,5% hiperbarik merupakan anestetik lokal golongan amino amida yang paling banyak digunakan pada teknik anestesi spinal.…”
Section: Pendahuluanunclassified